(untitled) (Biological Sciences - PJSIR, 2002)
A bimolecular reaction was studied between monochloroacetate and sodium thi osulphate ions i n the presence of magnesium chloride. The temperature dependence of rate constant was eval uated at 40-70 °C. The val ues of activation energy (E) and activation parameter s such as chan ge i n enthalpy of activation (6 H ;t) , change i n entropy of activation (6 S ;t), and change in free energy of activation (6 G ;o) were estimated as a function of ionic stren gth (µ) of the mediu m .